BCR-ABL1-negative chronic myeloid neoplasms: an update on management techniques. (May 2012) - Vannucchi, Alessandro M; Pieri, Lisa; Susini, Maria Chiara; Guglielmelli, Paola
Recent discoveries concerning mutations associated with chronic myeloproliferative neoplasms have modified our understanding of the biology of these incurable diseases and guided us to the development of inhibitors active on the constitutively activated JAK–STAT pathway. Concurrently, numerous studies dealt with clinical issues; it led to a revised WHO classification; clarified the role of mutated JAK2 and leukocytosis in the pathogenesis of cardiovascular events; allowed the development of risk prognostic scores and tools for monitoring response to therapy; and resulted in completion of Phase III trials with JAK2 inhibitor in myelofibrosis. All these results hold the promise of improving patient prognostication and therapeutic approach, with the aim of efficiently preventing disease-associated complications and, hopefully, to improve the dismal survival associated with myelofibrosis. This review discusses how to manage, according to current clinical practice, the steps of diagnosis, prognostication and therapeutic choices in myeloproliferative neoplasm patients.